Pengembangan Bahan Ajar Biologi Dengan Menggunakan Modul Berbasis Karakter Menurut Al–Quran Pada Materi Sistem Reproduksi di SMA Kelas XI IPA - Halimatussa'diah Halimatussa'diah; Meilinda Meilinda (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2015)
Abstract: The The development of biology module based on the character from the holy Qur’an of the 11th grades of Senior high school had done to create valid and effective module. Type of this study is development research that has three phases according to Akker, which are analysis, design and evaluation. The evaluation of the module was done at SMA Islam Terpadu Raudhatul Ulum on even semester 2013-2014. The techniques use to collect the data were documentation, validation sheet of teaching material, test and questionnaire. Based on the data gained and interpreted, the result show that (1) from the documentation and interview, it was found that in SMA IT RU on biology subject, the teacher has not used teaching material based on the holy Qur’an. (2) from the data validation by the expert. It was found that the teaching material that was developed is valid in term of media, language, material and interpretation of the subsections of the holy Qur’an. (3) from the questionnaire written by students, it was found that the teaching material is very good. (4) from the result of the test, it showed that the teaching material is effective. Based on the result of the data collection, it can be concluded that the teaching material product is valid and effective that having through analysis, design, and evaluation. Keywords : development research, character, the holy Qur’an, valid, effective.